The Growth and Decay of Intense GNSS Amplitude and Phase Scintillation During Non‐Storm Conditions - Mahith Madhanakumar; Andres Spicher; Juha Vierinen; Kjellmar Oksavik; Anthea J. Coster; Devin Ray Huyghebaert; Carley J. Martin; Ingemar Häggström; Larry J. Paxton (Space Weather)
Abstract A multi‐instrument study is conducted at the dayside polar ionosphere to investigate the spatio‐temporal evolution of scintillation in Global Navigation Satellite System (GNSS) signals during non‐storm conditions. Bursts of intense amplitude and phase scintillation started to occur at ∼ 9 MLT and persisted for more than 1 hour implying the simultaneous existence of Fresnel and large‐scale sized irregularities of significant strength in the pre‐noon sector. Measurements from the EISCAT radar in Svalbard (ESR) revealed the presence of dense plasma structures with significant gradients in regions of strong Joule heating/fast flows and soft precipitation when scintillation was enhanced. Plasma structuring down to Fresnel scales were observed both in the auroral oval as well as inside the polar cap with the associated amplitude scintillation exhibiting similar strengths regardless of whether the density structures were in regions of active auroral dynamics or not. The observations are placed within the context of different sources of free energy, providing insights into the important mechanisms that generate irregularities capable of perturbing GNSS signal properties in the dayside ionosphere. Furthermore, a strong negative excursion in the interplanetary magnetic field (IMF) By component during the northward turning of Bz led to the transport of a depleted region of plasma density into the post‐noon sector that significantly weakened both amplitude and phase scintillation.